Analysis of the duration of compliance between recidivism of drunk driving and reinstatement of license after suspension or revocation. (March 2019) - Choi, Yoon-Young; Kho, Seung-Young; Kim, Dong-Kyu; Park, Byung-Jung
Highlights: License suspension and revocation are sanctions for specific deterrence of DUI. Drivers' characteristics are the sources of improving the deterrence effect. We suggest the framework to explore the compliance duration of the sanctions. We provide case studies using large-scale data of newly-licensed drivers in Korea. The results provide the violation-prone group and policy implication of variable fines. Abstract: The objective of this study was to examine the specific deterrence effect of administrative license suspension and revocation regarding the duration of compliance. This study tried to capture the effort of the reinstated offenders to increase the duration of their compliance in spite of their subsequent conviction for DUI. Specifically, the difference between the recidivism rate and the duration of compliance was examined and compared in terms of drivers' characteristics, including gender, the type of license, and age. Data from all drivers who have been newly licensed for five years from 2009 to 2014 in Korea were collected for analysis. The proportional hazard regression and logistic regression models were estimated for the drivers with suspended or revoked licenses, respectively. The former was for exploring the duration of compliance, and the latter was for analyzing the recidivism rate. The results of the analysis showed that license sanctions significantly increased the duration of compliance. The results indicated that the violation-prone groups included male drivers, those with regular and moped licenses, and those between the ages of 30 and 39. License suspension was more effective than license revocation, but this finding did not hold for regular licensed drivers. Drivers' groups that showed different results between compliance duration and recidivism rate also were identified and appropriate treatments should be implemented to improve their willingness to comply.